Materialistic Strife and Its Impact on Andalusian Society: Luxury Among the Kings of the Taifas as a Model (422–483 AH / 1031–1091 CE) (Journal of human and social sciences, 2023)
The phenomenon of materialistic strife worsened, especially during the era of the Taifa kings, and it continued extensively, leading to boasting and displays of pomp and luxury, even competing with neighboring kings and the aristocracy. Naturally, these classes were characterized by excessive wealth, leading them to waste public funds on all life's pleasures. Under these tumultuous transformations, the door was opened to the spread of unreasonable luxury, and literature reflected this prevailing lifestyle, resulting in an increase in poems and poetry gatherings. Thus, the fifth Hijri century (eleventh century CE) was considered the beginning of the dissolution of Umayyad cohesion and a warning of worse to come.
Keywords: Material Greed; Taifa Kings; Luxury and Extravagance; Andalusian Society; Poetry and Literature